Colouring activities untuk mereduksi agresivitas pada siswa kelas 3 SD - Najwa Maharani Zahra; Tiara Marsela Triyani; Syifa Aryani; Harta Prima Meza; Muhammad Firly (Departemen Psikologi, Universitas Negeri Padang, 2024)
The research design used in this study was two- group posttes design. The population in this study were 3rd grade students in one of the public elementary schools in Padang City. The sample in this study amounted to 30 people in which, the sample was divided into two groups, namely the coloring and non-coloring groups, so that it was obtained in one group of 15 samples. The analysis techniques used include normality test, homogeneity test and hypothesis testing using t-test, where the results are processed using the JASP 16.0 application. The results obtained are that there is a significant difference in aggression levels between classes given coloring activities and classes that are not given coloring activities because the p value = 0.001.